PROFIL SURJA HUBUNG KARENA PROSES ENERGIZED (PEMBERIAN TENAGA) PADA SALURAN TRANSMISI 500 KV - Yuniarto, Yuniarto (Vocational School Diponegoro University, 2010)
Yuniarto, in this paper explain that transient over voltage that happened because switching surge have tobe paid attention to don't cause the damage equipments of insulation coordination system. This research aim toperceive the transient over voltage at the end of 500 kv transmission line caused energized process by using EMTP(Electromagnetic Transients Program) as toll to simulate the energized process. Data for this research was takenfrom 500 kv transmission line Ungaran-Pedan. From this research was expected can become a reference for powercompany in planning insulation coordination at transmission line.Result of research show that transient over voltage at the end of 500 kv transmission line caused energizedprocess reach more or less twice its nominal voltageKey word : energized, karateristik, transient over voltage, EMTP